Binding of quinidine radically increases the stability and decreases the flexibility of the cytochrome P450 2D6 active site - Berka, Karel; Anzenbacherová, Eva; Hendrychová, Tereza; Lange, Reinhard; Mašek, Vlastimil; Anzenbacher, Pavel; Otyepka, Michal (Journal of inorganic biochemistry, 2012)
Human cytochrome P450 2D6 (CYP2D6) is an enzyme of the CYP superfamily responsible for biotransformation of about 20% of drugs of known metabolism containing a basic nitrogen and a planar aromatic ring. Here, we present a combined experimental and computational study on the compressibility and flexibility of unliganded and quinidine-bound CYP2D6. Experimentally, high-pressure induced Soret band shifts of the enzyme were measured by UV/VIS spectroscopy, while 100 ns all atomic molecular dynamics (MD) simulations in explicit water were used in the computational analysis. We identified sharp differences between ligand-free and quinidine-bound CYP2D6 forms in compressibility, flexibility parameters and active site solvation. While the unliganded CYP2D6 is compressible, quinidine binding significantly rigidifies the CYP2D6 active site. In addition, MD simulations show that quinidine binding results in pronounced reductions in active site flexibility and solvation.
Keywords: vazba proteinů; cytochrom P-450 CYP2D6; lidé; Enzyme Stability; chinidin; Cytochrome P-450 CYP2D6; katalytická doména; spektrofotometrie ultrafialová; Protein Binding; Catalytic Domain; Spectrophotometry, Ultraviolet; stabilita enzymů; Quinidine; Humans